High-coating-bonding-strength netted sandwich cloth with gradient interface reinforcing structure and preparation method of high-coating-bonding-strength netted sandwich cloth

By performing surface roughening treatment on high-performance fabrics and applying layers such as thermoplastic fiber glue mesh and nonwoven fiber felt, a gradient interface reinforcement structure is formed, which solves the problem of insufficient interface bonding between aramid fiber and thermoplastic polymer, and significantly improves the mechanical properties of the clamped mesh fabric.

CN119682337AActive Publication Date: 2025-03-25TIANJIN FIRE SCI & TECH RES INST OF MEM
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510191661.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-03-25
Estimated Expiration
2045-02-21

AI Technical Summary

Technical Problem

In the prior art, the interface bond between aramid fiber and thermoplastic polymer is insufficient, resulting in poor mechanical properties of composite materials and difficult to meet high performance requirements.

Method used

By roughening the surface of the fibers in high-performance fabrics, micro-nano-scale fiber whiskers are formed, and thermoplastic fiber webs and nonwoven fiber felts are applied to the surface of the fabric, combining with the thermoplastic polymer film layer to form a gradient interface reinforced structure.

Benefits of technology

It significantly improves the interface bonding strength between aramid fiber and polymer matrix, improves the coating bonding strength and tear resistance of the clamp cloth, and meets the needs of high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119682337A_ABST
    Figure CN119682337A_ABST
Patent Text Reader

Abstract

The invention provides a high-coating-bonding-strength netted sandwich cloth with a gradient interface reinforcing structure and a preparation method of the netted sandwich cloth, and belongs to the technical field of coated fabrics. The netted sandwich cloth is composed of a plurality of layers of materials, and comprises a thermoplastic fiber glue net 1, a non-woven fiber felt, a thermoplastic fiber glue net 2 and a thermoplastic polymer film layer which are symmetrically arranged in sequence by taking a high-performance fabric as a central layer, wherein the high performance fabric exerts tensile, puncture performance advantages, and the non-woven fibrofelt provides tear performance advantages. Micro-nano fibers are generated through surface roughening treatment of high-performance fibers, interface transition between the high-performance fibers and a polymer matrix is achieved in combination with the non-woven fiber felt, namely, the micro-nano fibers in the high-performance fabric and fibers in the non-woven fiber felt are used for providing a gradient interface structure, and therefore the bonding strength of the coating is improved. Interface bonding between high-performance fibers and a polymer matrix is achieved through multi-mechanism combination, and meanwhile the tearing strength of the non-woven fiber felt can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coated fabrics, in particular to a high-coating bonding strength sandwich fabric with a gradient interface enhancement structure and a preparation method thereof. Background Art

[0002] At present, polymer-coated polyester fabrics are widely used in the fields of industry and protective materials due to their low cost and high durability. However, their mechanical properties such as tensile, tearing and puncture resistance are poor, making it difficult to meet high-performance requirements. Para-aramid is a chain-like polymer material with high strength and high modulus. It has excellent dimensional stability, impact resistance, chemical resistance and excellent heat resistance, and is widely used as a reinforcing fiber for advanced composite materials. However, aramid has high crystallinity, lacks polar groups on the surface and has a smooth surface, which makes its surface energy low and its surface wettability poor, which is not conducive to the bonding between aramid and the matrix resin, resulting in the formation of interface defects between aramid and the polymer matrix, limiting the performance of the composite material. At present, the surface modification methods of aramid mainly include plasma treatment, high-energy ray treatment, chemical etching, surface grafting, surface coating, etc. Invention patent CN202010824820.8 discloses an aramid fiber coated with PUR on the surface and a preparation method thereof. The aramid fiber is immersed in a hot-melt moisture-curing reactive polyurethane hot melt adhesive. After the PUR on the surface of the aramid fiber is heated and melted, the self-adhesion of the aramid fiber can be achieved, and the surface adhesion between the aramid fiber and other substrates can be improved. Although the surface energy of the aramid fiber coated with PUR is improved, the interface bonding between the original aramid fiber and the surface PUR coating layer has not been fundamentally improved. During the load-bearing process, the aramid fiber and the PUR coating are prone to peeling. Therefore, it is necessary to design the interface bonding between aramid and thermoplastic polymers to achieve strong interface bonding between aramid and polymer matrix. The surface of aramid fiber is smooth. Constructing a rough structure on the aramid surface to improve its embedded bonding with the polymer matrix is ​​an effective way to improve the interface bonding between the two. A typical method is to deposit nanoparticles on the aramid surface, such as nano-polyacrylonitrile, carbon, and nano-SiO 2 、TiO 2 and zinc oxide, but the deposited nanoparticles are usually combined with aramid fibers through physical adsorption or weak chemical bonds, the nanoparticles are easy to fall off, and there are certain difficulties in controlling the uniformity and thickness of the deposited layer, especially when the nanoparticles are large in size or unevenly distributed. Excessive nanoparticle deposition may lead to an increase in the thickness of the interface layer, thereby producing a stress concentration effect at the interface and affecting the mechanical properties of the composite fiber material. Summary of the invention

[0003] The object of the present invention is to provide a mesh cloth with high coating bonding strength and a gradient interface enhancement structure and a preparation method thereof, which can improve the coating bonding strength of the mesh cloth.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a mesh cloth with high coating bonding strength and a gradient interface enhancement structure, comprising the following steps: The high-performance fabric is ultrasonically compounded with an alkali solution and an organic solvent, and the surface is roughened to obtain a high-performance fabric with a micro-nano structure; the high-performance fiber used in the high-performance fabric includes one or more of aramid fiber, polybenzimidazole fiber, polyimide fiber, polyetheretherketone fiber and polyhydrazide fiber; Applying a first thermoplastic fiber adhesive web on the surface of the high-performance fabric having the micro-nano structure to obtain a high-performance fabric covered with the fiber adhesive web; After applying a non-woven fiber felt to the surface of the high-performance fabric covered with the fiber glue web, a first heat pressing treatment is performed, and then a second thermoplastic fiber glue web is applied to the surface of the non-woven fiber felt to obtain a composite mesh; A thermoplastic polymer film is applied on the surface of the composite mesh cloth, and a second hot pressing treatment is performed to obtain a mesh cloth with a gradient interface enhancement structure and high coating bonding strength.

[0005] Preferably, the parameters of the high performance fabric include: surface density of 150-500 g / m 2 The filament yarn used is 800~1800D, the warp and weft yarn densities are 15~30 yarns / inch respectively, and the fabric structure is plain or twill.

[0006] Preferably, the alkali solution includes one or more of potassium hydroxide solution, sodium hydroxide solution and ammonia solution; the organic solvent includes one or more of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide; the volume ratio of the alkali solution to the organic solvent is 1-3:100, and the concentration of the alkali solution is 0.1-0.2 g / mL.

[0007] Preferably, the surface roughening treatment time is 1-4 hours; the ultrasonic frequency of the ultrasonic compound is 20-30 kHz, and the stirring speed is 300-800 rpm.

[0008] Preferably, the surface density of the first thermoplastic fiber rubber web and the second thermoplastic fiber rubber web is independently 30-50 g / m 2 .

[0009] Preferably, the first thermoplastic fiber rubber web and the second thermoplastic fiber rubber web are both prepared by melt-blown nonwoven molding.

[0010] Preferably, in terms of mass percentage, the raw materials for preparing the first thermoplastic fiber adhesive web and the second thermoplastic fiber adhesive web include: 50-70% ethylene-vinyl acetate copolymer, 10-20% polyurethane and 20-30% copolyester.

[0011] Preferably, the nonwoven fiber felt is prepared by thermal bonding nonwoven molding of polyester fiber and high-strength fiber, the high-strength fiber includes aramid fiber and / or glass fiber, the mass ratio of the polyester fiber to the high-strength fiber is 20:80-50:50, and the surface density of the nonwoven fiber felt is 20-60 g / m 2 .

[0012] Preferably, the conditions of the first hot pressing treatment include: pressure of 0.5-0.8 MPa, temperature of 150-180°C, and time of 0.5-1 min; The conditions of the second hot pressing treatment include: a pressure of 0.5-0.8 MPa, a temperature of 140-160° C., and a time of 1-2 min.

[0013] The present invention provides a mesh cloth with high coating bonding strength and a gradient interface enhancement structure prepared by the preparation method described in the above technical solution.

[0014] The present invention provides a method for preparing a high coating bonding strength sandwich cloth with a gradient interface enhancement structure. The sandwich cloth of the present invention is composed of multiple layers of materials, including a high-performance fabric as a central layer, a thermoplastic fiber glue net 1, a non-woven fiber felt, a thermoplastic fiber glue net 2 and a thermoplastic polymer film layer symmetrically arranged in sequence; wherein the high-performance fabric plays the advantages of tensile and puncture performance, and the non-woven fiber felt provides the advantages of tearing performance. Micro-nano fibers are produced by roughening the surface of the high-performance fiber itself, and the interface transition between the high-performance fiber and the polymer matrix is ​​achieved by combining the non-woven fiber felt, that is, the micro-nano fibers in the high-performance fabric and the fibers in the non-woven fiber felt provide a gradient interface structure, thereby improving the coating bonding strength. The present invention realizes the interface bonding between the high-performance fiber and the polymer matrix through the combination of multiple mechanisms, and the non-woven fiber felt can also improve the tear strength.

[0015] Compared with the prior art, the present invention has significant advantages in the following aspects: The present invention roughens the surface of the fibers in the high-performance fabric, thereby producing surface active sites generated by chemical etching of the fibers on the one hand, and forming nanometer-scale fiber whiskers on the fiber surface on the other hand, thereby producing a mechanical locking effect with the polymer matrix (thermoplastic polymer film layer) or the thermoplastic fiber adhesive web, and significantly improving the interface bonding performance.

[0016] The addition of non-woven fiber felt in the present invention can solve the problem of insufficient tear strength after high-performance fibers are compounded with thermoplastic polymer matrix. The non-woven material is an isotropic material. By applying non-woven fiber felt on the surface of high-performance fabric, stress can be dispersed in multi-axial directions, thereby improving durability and anti-destruction performance, improving tear resistance, and meeting high tear performance application requirements.

[0017] The present invention uses a thermoplastic fiber adhesive web as the adhesive layer, and its thermoplastic fibers are of micron or submicron scale. Under the high temperature conditions of hot pressing and compounding the high-performance fabric and the thermoplastic fiber adhesive web, the micron or submicron scale thermoplastic fibers melt, which can achieve better penetration into the fiber bundles in the high-performance fiber plain weave fabric, and then form a better interface bonding with the high-performance fibers, thereby obtaining high coating bonding strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic structural diagram of a high coating bonding strength sandwich cloth with a gradient interface enhancement structure of the present invention; Figure 2 This is a schematic diagram of the micro-nano anchor point structure on the surface of aramid fabric in Example 1 of the present invention; Figure 3 This is a SEM image of the aramid fabric with micro-nano structure in Example 1 of the present invention; Figure 4 This is a schematic diagram of the aramid fiber that has not been treated with alkali solution and organic solvent in Comparative Example 1 of the present invention; Figure 5 This is a SEM image of the aramid fiber in Comparative Example 1 of the present invention that has not been treated with alkali solution and organic solvent; Figure 6 This is a schematic diagram of the structure of the mesh cloth without the non-woven fiber felt layer in Comparative Example 2 of the present invention; Among them, 1. high-performance fabric; 1-1. high-performance fiber; 1-2. micro-nano anchor point structure on the surface of high-performance fiber; 2. thermoplastic fiber rubber net 1; 3. non-woven fiber felt; 4. thermoplastic fiber rubber net 2; 5. thermoplastic polymer film. DETAILED DESCRIPTION

[0019] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0020] The present invention provides a method for preparing a mesh cloth with high coating bonding strength and a gradient interface enhancement structure, comprising the following steps: The high-performance fabric is ultrasonically compounded with an alkali solution and an organic solvent, and the surface is roughened to obtain a high-performance fabric with a micro-nano structure; the high-performance fiber used in the high-performance fabric includes one or more of aramid fiber, polybenzimidazole fiber, polyimide fiber, polyetheretherketone fiber and polyhydrazide fiber; Applying a first thermoplastic fiber adhesive web on the surface of the high-performance fabric having the micro-nano structure to obtain a high-performance fabric covered with the fiber adhesive web; After applying a non-woven fiber felt to the surface of the high-performance fabric covered with the fiber glue web, a first heat pressing treatment is performed, and then a second thermoplastic fiber glue web is applied to the surface of the non-woven fiber felt to obtain a composite mesh; A thermoplastic polymer film is applied on the surface of the composite mesh cloth, and a second hot pressing treatment is performed to obtain a mesh cloth with a gradient interface enhancement structure and high coating bonding strength.

[0021] The invention ultrasonically compounds the high-performance fabric with alkali solution and organic solvent, performs surface roughening treatment, and obtains the high-performance fabric with micro-nano structure.

[0022] In the present invention, the high-performance fibers used in the high-performance fabric include one or more of aramid fibers, polybenzimidazole fibers, polyimide fibers, polyetheretherketone fibers and polyhydrazide fibers, and aramid fibers are more preferred; when the high-performance fabric contains two or more of the above fibers, the present invention has no special limitation on the ratio of different types of fibers, and can be adjusted according to actual needs.

[0023] In the present invention, the parameters of the high performance fabric preferably include: surface density of 150-500 g / m 2 , more preferably 240~400g / m 2 , more preferably 280~300g / m 2 The fineness of the filament yarn used is 800~1800D, more preferably 1000~1500D, the warp and weft yarn densities are independently 15~30 yarns / inch, more preferably 18~24 yarns / inch, and further preferably 20~22 yarns / inch, and the fabric structure is plain or twill.

[0024] The present invention has no particular limitation on the source of the high-performance fabric, and any commercially available product known in the art may be used.

[0025] In the present invention, the alkali solution preferably includes one or more of potassium hydroxide solution, sodium hydroxide solution and ammonia solution; the organic solvent preferably includes one or more of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide; the volume ratio of the alkali solution to the organic solvent is preferably 1-3:100, more preferably 2:100, and the concentration of the alkali solution is preferably 0.1-0.2 g / mL, more preferably 0.15 g / mL.

[0026] In the present invention, the surface roughening treatment time is preferably 1-4 h, more preferably 1-2 h; the ultrasonic frequency of the ultrasonic compound is preferably 20-30 kHz, more preferably 20-25 kHz, and the stirring speed is preferably 300-800 rpm, more preferably 500-600 rpm.

[0027] The present invention uses a mixture of alkali solution and organic solvent to treat high-performance fabrics, and under the action of ultrasonic cavitation and mechanical stirring, the surface of the high-performance fiber is fibrillated, a fibrillated surface micro-nano anchor point structure is formed on the surface of the fabric, and micro-nano rough structure construction is achieved.

[0028] After obtaining the high-performance fabric with micro-nano structure, the present invention applies a first thermoplastic fiber adhesive web on the surface of the high-performance fabric with micro-nano structure to obtain the high-performance fabric covered with the fiber adhesive web.

[0029] In the present invention, the raw materials for preparing the first thermoplastic fiber adhesive web and the second thermoplastic fiber adhesive web independently include: 50-70% ethylene-vinyl acetate copolymer (EVA), 10-20% polyurethane (PU) and 20-30% copolyester (Co-PES), calculated by mass percentage.

[0030] In the present invention, the first thermoplastic fiber rubber web and the second thermoplastic fiber rubber web are preferably prepared by melt-blown nonwoven molding. The method for forming the melt-blown nonwoven of the present invention is preferably: using a twin-screw mixer to uniformly mix EVA, PU and Co-PES, and using a twin-screw extruder for melt extrusion and forming to obtain a thermoplastic fiber rubber web; the feeding section temperature of the twin-screw extruder is 150-170°C, the compression section temperature is 180-200°C, the homogenization section temperature is 200-220°C, the rotation speed is 100-200 rpm, and the pressure is 5-10 MPa; the melt-blowing spinneret diameter is 0.2-0.4 mm, the spinneret temperature is 210-240°C, the air temperature is 230-270°C, and the air pressure is 0.6-1.2 MPa. The feeding section temperature of the twin-screw extruder is more preferably 160-170°C, the compression section temperature is more preferably 185-190°C, the homogenization section temperature is more preferably 200-210°C, the rotation speed is more preferably 120-150 rpm, and the pressure is more preferably 8-10 MPa; the melt-blowing spinneret diameter is more preferably 0.2-0.3 mm, the spinneret temperature is more preferably 220-230°C, the air temperature is more preferably 250-260°C, and the air pressure is more preferably 1 MPa.

[0031] In the present invention, the surface density of the first thermoplastic fiber rubber web and the second thermoplastic fiber rubber web is preferably 30-50 g / m 2, more preferably 50g / m 2 In the present invention, the thermoplastic fiber adhesive web is used as the adhesive layer, and the surface density of the entire sandwich fabric after compounding is controlled by the surface density.

[0032] The present invention has no special limitation on the application method, and the first thermoplastic fiber glue web is laid on the surface of the high-performance fabric with micro-nano structure.

[0033] In the present invention, the addition amount of the first thermoplastic fiber adhesive web or the second thermoplastic fiber adhesive web is preferably adjusted by gram weight, and adhesive webs of different gram weights are produced according to demand. Multiple layers of low-gram weight fiber adhesive webs can be applied, or a single layer of high-gram weight fiber adhesive web can be applied to meet the coating bonding strength requirements.

[0034] In the present invention, the first thermoplastic fiber adhesive web or the second thermoplastic fiber adhesive web are preferably the same.

[0035] After obtaining the high-performance fabric covered with fiber glue net, the present invention applies a non-woven fiber felt on the surface of the high-performance fabric covered with fiber glue net, performs a first heat pressing treatment, and then applies a second thermoplastic fiber glue net on the surface of the non-woven fiber felt to obtain a composite mesh cloth.

[0036] In the present invention, the nonwoven fiber felt is preferably prepared by thermal bonding nonwoven molding of polyester fibers and high-strength fibers, the high-strength fibers preferably include aramid fibers and / or glass fibers, and the mass ratio of the polyester fibers to the high-strength fibers is preferably 20:80 to 50:50, more preferably 20:80.

[0037] The present invention preferably mixes polyester fiber and high-strength fiber uniformly, and then performs opening, carding and thermal bonding in sequence to obtain a nonwoven fiber felt. The present invention utilizes the thermoplasticity of polyester fiber and softens or melts the polyester fiber by heating to achieve mutual bonding of the fibers.

[0038] The present invention has no particular limitation on the opening and combing, and the opening and combing can be carried out according to processes well known in the art.

[0039] The present invention preferably adopts a hot rolling method to thermally bond the polyester fiber and the high-strength fiber to fix the web. The conditions of the hot rolling method are preferably: upper roller temperature: 120~160°C, lower roller temperature: 110~140°C, pressure: 0.5~2MPa, the upper roller temperature is more preferably 140~160°C, the lower roller temperature is more preferably 120~140°C, and the pressure is more preferably 1.0~1.5MPa.

[0040] In the present invention, the surface density of the nonwoven fiber mat is preferably 20 to 60 g / m 2 , more preferably 30 to 50 g / m 2 .

[0041] The present invention has no particular limitation on the method of applying the non-woven fiber mat. The non-woven fiber mat can be directly laid on the high-performance fabric covered with the viscose web in a manner well known in the art.

[0042] In the present invention, the conditions of the first hot pressing treatment preferably include: a pressure of 0.5-0.8 MPa, more preferably 0.6-0.75 MPa; a temperature of 150-180°C, more preferably 150-160°C, and a time of 0.5-1 min, more preferably 0.5-0.8 min.

[0043] In order to improve the peeling strength, the present invention applies a thermoplastic fiber glue net as a melt-blown layer on the surface of the non-woven fiber felt, and the melt-blown layer is coated on the surface of the non-woven fiber felt.

[0044] After obtaining the composite mesh cloth, the present invention applies a thermoplastic polymer film on the surface of the composite mesh cloth and performs a second hot pressing treatment to obtain a mesh cloth with a high coating bonding strength and a gradient interface enhancement structure.

[0045] In the present invention, the thermoplastic polymer film is preferably a PVC film or a TPU film; the surface density of the thermoplastic polymer film is preferably 100-300 g / m 2 , more preferably 200 to 300 g / m 2 The present invention uses a thermoplastic polymer film as the surface film material of the mesh material, so that the mesh material has waterproof, sealing and decorative properties. The present invention has no special limitation on the thermoplastic polymer film and its source, and any thermoplastic polymer film for mesh known in the art can be used.

[0046] The present invention has no particular limitation on the method of applying the thermoplastic polymer film. The thermoplastic polymer film can be directly laid on the surface of the composite mesh in a manner well known in the art.

[0047] In the present invention, the conditions of the second hot pressing treatment preferably include: a pressure of 0.5-0.8 MPa, more preferably 0.6-0.75 MPa; a temperature of 140-160° C., more preferably 145-160° C.; and a time of 1-2 min, more preferably 2 min.

[0048] In the preparation method of the present invention, the surface roughening treatment, applying a first thermoplastic fiber glue net on the surface of the high-performance fabric, applying a non-woven fiber felt on the surface of the high-performance fabric covered with the fiber glue net, applying a second thermoplastic fiber glue net on the surface of the non-woven fiber felt, and applying a thermoplastic polymer film on the surface of the composite mesh are all double-sided surfaces, forming a structure such as Figure 1 High coating adhesion strength sandwich fabric with gradient interface reinforcement structure shown.

[0049] The present invention provides a mesh cloth with high coating bonding strength and a gradient interface enhancement structure prepared by the preparation method described in the above technical solution.

[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention. Example 1

[0051] 1) Aramid fabric is woven with aramid filament yarn, and the surface density of aramid fabric is 280g / m 2 The fineness of the filament yarn used is 1000D, the density of the warp and weft yarns is 22 yarns / inch, and the fabric structure is plain weave; Aramid fabric was ultrasonically treated with a mixture of 0.15 g / mL potassium hydroxide aqueous solution and dimethyl sulfoxide, the volume ratio of alkali solution to organic solvent was 2:100, the treatment time was 1 h, the ultrasonic frequency was 20 kHz, and the magnetic stirring speed was 600 rpm to obtain an aramid fabric with a micro-nano structure, such as Figure 2 As shown; 2) A nonwoven fiber felt was prepared by a thermal bonding nonwoven forming method. The nonwoven fiber felt was made of polyester fiber and glass fiber. The mass ratio of polyester fiber to glass fiber was 20:80. The polyester fiber and glass fiber were evenly mixed, opened and combed in sequence, and then thermally bonded and fixed by a hot rolling method. The upper roller temperature was 160°C, the lower roller temperature was 140°C, and the pressure was 1.5 MPa. A nonwoven fiber felt with a surface density of 30 g / m 2 ; 3) Gluing and compounding: in the thermoplastic fiber rubber web, EVA (molecular weight 25000 g / mol) accounts for 50% by weight, PU (molecular weight 50,000 g / mol) accounts for 20% by weight, and Co-PES (molecular weight 30000 g / mol) accounts for 30% by weight. A twin-screw mixer is used to evenly mix EVA, PU and Co-PES, and melt-extrude and mold them in a twin-screw extruder. The feeding section temperature of the twin-screw extruder is 170°C, the compression section temperature is 185°C, the homogenization section temperature is 210°C, the rotation speed is 120 rpm, and the pressure is set to 10 MPa; the melt-blowing spinneret has a diameter of 0.2 mm, a spinneret temperature of 230°C, an air temperature of 250°C, and an air pressure of 1 MPa, to obtain a thermoplastic fiber rubber web, which is used as thermoplastic fiber rubber web 1 or thermoplastic fiber rubber web 2; The surface density of the aramid fabric with micro-nano structure is 50g / m 2 Thermoplastic fiber rubber net 1, then the non-woven fiber felt is laid on the surface of the rubber net, and after the first step of hot pressing, the pressure is 0.75MPa, the temperature is 150℃, and the time is 0.5min; then the non-woven fiber felt with a surface density of 50g / m2 Thermoplastic fiber glue web 2 is the same as thermoplastic fiber glue web 1; then the surface density is 200g / m 2 The PVC film is laid on the surface of the thermoplastic fiber rubber mesh 2, and after the second step of hot pressing treatment, the pressure is 0.75MPa, the temperature is 145℃, and the time is 2min, the composite is completed to obtain a high coating bonding strength sandwich cloth with a gradient interface reinforcement structure. Example 2

[0052] 1) Aramid fabric is woven with aramid filaments, and the surface density of the aramid fabric is 300g / m 2 The fineness of the filament yarn used is 1500D, the density of the warp and weft yarns is 20 yarns / inch, and the fabric structure is plain weave; The aramid fabric was ultrasonically treated with a mixture of 0.15 g / mL potassium hydroxide aqueous solution and dimethyl sulfoxide, the volume ratio of alkali solution to organic solvent was 2:100, the treatment time was 1 h, the ultrasonic frequency was 20 kHz, and the magnetic stirring speed was 600 rpm to obtain an aramid fabric with a micro-nano structure.

[0053] 2) A nonwoven fiber felt is prepared by a thermal bonding nonwoven forming method. The nonwoven fiber felt is made of polyester fiber and aramid fiber. The mass ratio of polyester fiber to aramid fiber is 20:80. The polyester fiber and the glass fiber are evenly mixed, opened and combed in sequence, and then thermally bonded to form a solid network by a hot rolling method. The upper roller temperature is 160°C, the lower roller temperature is 140°C, the pressure is 1.5MPa, and the surface density of the nonwoven fiber felt is 50g / m 2 .

[0054] 3) Gluing and compounding: in the thermoplastic fiber rubber web, EVA (molecular weight 25000 g / mol) accounts for 50% by weight, PU (molecular weight 50,000 g / mol) accounts for 20% by weight, and Co-PES (molecular weight 30000 g / mol) accounts for 30% by weight. A twin-screw mixer is used to evenly mix EVA, PU and Co-PES, and melt-extrude and mold them in a twin-screw extruder. The feeding section temperature of the twin-screw extruder is 170°C, the compression section temperature is 185°C, the homogenization section temperature is 210°C, the rotation speed is 120 rpm, and the pressure is set to 10 MPa; the melt-blowing spinneret has a diameter of 0.2 mm, a spinneret temperature of 230°C, an air temperature of 250°C, and an air pressure of 1 MPa, to obtain a thermoplastic fiber rubber web, which is used as thermoplastic fiber rubber web 1 or thermoplastic fiber rubber web 2; The surface density of the aramid fabric with micro-nano structure is 50g / m 2Thermoplastic fiber glue net 1; then the non-woven fiber felt is laid on its surface, and after the first step of hot pressing, the pressure is 0.75MPa, the temperature is 150℃, and the time is 0.5min; then the non-woven fiber felt with a surface density of 50g / m 2 Thermoplastic fiber glue web 2 is the same as thermoplastic fiber glue web 1; then the surface density is 200g / m 2 The PVC film is laid on the surface of the thermoplastic fiber rubber mesh 2, and after the second step of hot pressing treatment, the pressure is 0.75MPa, the temperature is 145℃, and the time is 2min, the composite is completed to obtain a high coating bonding strength sandwich cloth with a gradient interface reinforcement structure.

[0055] Comparative Example 1 The only difference from Example 1 is that the aramid fabric has not been treated with alkali solution and organic solvent, and the aramid fiber structure is as follows: Figure 4 shown.

[0056] Comparative Example 2 The difference from Example 1 is that: no non-woven fiber felt layer is provided, and the structure includes 2-thermoplastic fiber rubber net 1 and 5-PVC film symmetrically arranged in sequence with aramid fabric as the central layer, and the structure is as follows: Figure 6 shown.

[0057] Characterization and performance testing 1) Figure 3 is a SEM image of the aramid fabric with micro-nano structure in Example 1 of the present invention; Figure 3 It can be seen that micro-nano-scale fiber whiskers are formed on the surface of aramid fibers, which serve as micro-nano anchor point structures on the fibrillated surface. This structure increases the surface roughness of aramid fibers and can be interlocked with the thermoplastic adhesive mesh during the molding of the sandwich fabric to enhance the interface bonding effect.

[0058] 2) Figure 5 This is a SEM image of the aramid fiber described in Comparative Example 1 of the present invention that has not been treated with alkali solution and organic solvent; Figure 5 It can be seen that the aramid fiber has a smooth surface and no attachment points, making it difficult to form a firm fit with the thermoplastic adhesive mesh.

[0059] 3) Test the performance of the mesh cloth in Examples 1-2 and Comparative Examples 1-2: Tear strength test: HG_T 2581.1-2009 Determination of tear resistance of rubber or plastic coated fabrics Part 1_Constant tear rate method Peel strength test: HG T 3052-2008 Determination of adhesive strength of rubber or plastic coated fabric coatings The test results are shown in Table 1.

[0060] Table 1 Performance data of the mesh cloth in Examples 1-2 and Comparative Examples 1-2 Case Tear strength (N) Peel strength (N / 25mm) Example 1 751 63 Example 2 804 65 Comparative Example 1 703 52 Comparative Example 2 527 55 As shown in Table 1, the mesh cloth obtained in Example 1 has higher tear strength and peel strength; in Example 2, due to the use of thicker aramid filament bundles for weaving, the surface density of the prepared aramid fabric is higher than that of Example 1, and a non-woven fiber felt with higher surface density is used as a reinforcing layer, the tear resistance of the prepared mesh cloth is improved, and the peel strength is not significantly different from that of Example 1; in Comparative Example 1, the aramid fabric is not treated with alkali solution and organic solvent, the surface of the aramid fiber is smooth, and the bonding strength between the aramid fiber and the thermoplastic fiber rubber web is relatively weak, which not only affects the peel strength, but also improves the peel strength. Insufficient interface strength also causes the fibers of the mesh cloth to debond from the thermoplastic fiber mesh during the tearing process, thereby reducing the tear resistance. Comparative Example 2 does not have a non-woven fiber felt layer, and the tear resistance of the mesh cloth is mainly borne by the aramid fabric layer. Since the aramid fabric is woven by warp and weft interlacing, and is compounded with the thermoplastic fiber mesh and PVC, the mesh cloth is prone to stress concentration at the tear when it is subjected to a tearing load, resulting in insufficient tearing performance. Since the aramid fabric is treated with alkali solution and organic solvents, the peel strength of Comparative Example 2 is improved compared with Comparative Example 1.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high coating bonding strength sandwich fabric with a gradient interface enhancement structure, characterized in that: The following steps are involved: The high-performance fabric is ultrasonically compounded with an alkali solution and an organic solvent, and the surface is roughened to obtain a high-performance fabric with a micro-nano structure; the high-performance fiber used in the high-performance fabric includes one or more of aramid fiber, polybenzimidazole fiber, polyimide fiber, polyetheretherketone fiber and polyhydrazide fiber; Applying a first thermoplastic fiber adhesive web on the surface of the high-performance fabric having the micro-nano structure to obtain a high-performance fabric covered with the fiber adhesive web; After applying a non-woven fiber felt to the surface of the high-performance fabric covered with the fiber glue web, a first heat pressing treatment is performed, and then a second thermoplastic fiber glue web is applied to the surface of the non-woven fiber felt to obtain a composite mesh; A thermoplastic polymer film is applied on the surface of the composite mesh cloth, and a second hot pressing treatment is performed to obtain a mesh cloth with a high coating bonding strength and a gradient interface enhancement structure.

2. The preparation method according to claim 1, characterized in that: The parameters of the high performance fabric include: surface density of 150-500 g / m 2 The filament yarn used is 800~1800D, the warp and weft yarn densities are 15~30 yarns / inch respectively, and the fabric structure is plain or twill.

3. The preparation method according to claim 1, characterized in that: The alkali solution includes one or more of potassium hydroxide solution, sodium hydroxide solution and ammonia solution; the organic solvent includes one or more of dimethyl sulfoxide, N-methylpyrrolidone and N,N-dimethylformamide; the volume ratio of the alkali solution to the organic solvent is 1-3:100, and the concentration of the alkali solution is 0.1-0.2 g / mL.

4. The preparation method according to claim 1 or 3, characterized in that: The surface roughening treatment time is 1-4 hours; the ultrasonic frequency of the ultrasonic compound is 20-30 kHz, and the stirring speed is 300-800 rpm.

5. The preparation method according to claim 1, characterized in that: The surface density of the first thermoplastic fiber rubber web and the second thermoplastic fiber rubber web is independently 30-50 g / m 2 .

6. The preparation method according to claim 1 or 5, characterized in that: The first thermoplastic fiber rubber web and the second thermoplastic fiber rubber web are both prepared by melt-blown nonwoven molding.

7. The preparation method according to claim 6, characterized in that: Calculated by mass percentage, the raw materials for preparing the first thermoplastic fiber adhesive web and the second thermoplastic fiber adhesive web include: 50-70% ethylene-vinyl acetate copolymer, 10-20% polyurethane and 20-30% copolyester.

8. The preparation method according to claim 1, characterized in that: The nonwoven fiber felt is prepared by thermally bonding polyester fiber and high-strength fiber in a nonwoven molding method, wherein the high-strength fiber includes aramid fiber and / or glass fiber, the mass ratio of the polyester fiber to the high-strength fiber is 20:80-50:50, and the surface density of the nonwoven fiber felt is 20-60 g / m 2 .

9. The preparation method according to claim 1, characterized in that: The conditions of the first hot pressing treatment include: pressure of 0.5-0.8 MPa, temperature of 150-180°C, and time of 0.5-1 min; The conditions of the second hot pressing treatment include: a pressure of 0.5-0.8 MPa, a temperature of 140-160° C., and a time of 1-2 min.

10. A mesh cloth with high coating adhesion strength and a gradient interface enhancement structure prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Aramid fiber coated with PUR on surface and preparation method of aramid fiber

    CN111826963A

  • Strain coordination layer for integral forming of ablative thermal protection structure as well as preparation method thereof and application

    CN111136935A

  • Aramid fiber and carbon fiber mixed woven cloth

    CN111605259A

  • Basalt fiber / polypropylene composite material based on surface roughening and interface enhancement and preparation method of basalt fiber / polypropylene composite material

    CN113861460A

  • Fabric reinforced polymer composite material and preparation method thereof

    CN118181907A